Preparation of hybrid CuO/TiO₂ photocatalyst responsive towards UV-light (effect of incubation time) - Shanan, Nur Syuhada (2017)
Large amount of synthetic dyes are produced and consumed especially in a textile industry. Hence, Titanium dioxide (TiO₂) photocatalyst is one of the promising methods used in the treatment of dye removals. However, it has to be doped with other metals such copper oxide (CuO) to increase the efficiency under UV-light. This study was carried out to prepare hybrid CuO/TiO₂ using wet impregnation method by varying the incubation times at 1, 2, 4, 8 and 24 hr at 0.5wt% of copper concentration and 50˚C of incubation temperature. The next objective is to study the application of hybrid photocatalyst produce for degradation of dye in wastewater. Then, characterization of the photocatalyst was done by XRD, EDX, FESEM and BET analysis. Hybrid photocatalyst sample was prepared using Copper (II) acetate monohydrate as the precursor for copper loading. Photocatalytic degradation for 10 ppm of methyl orange was studied under UV-light irradiation and the extent of dye degradation was determined using UV-Vis Spectrophotometer. Thus, from the characterization analysis, XRD patterns exhibited strong diffraction peaks of pure anatase TiO₂. The copper loading cannot be detected by XRD analysis due to the low amount of copper content and beyond equipment limit but it can be found via EDX. The surface morphologies of bare TiO₂ and CuO/TiO₂ photocatalyst were studied by FESEM and indicated the relative uniform distribution of CuO on TiO₂. Apart from that, BET result showed no significant change on the surface area, pore volume and pore width for bare TiO2 and hybrid CuO/TiO₂ photocatalyst. Then, the result for the photocatalytic activity showed that the sample being incubated at 2 hr during preparation of hybrid photocatalyst is an optimal result as it showed the best decolourization results with 82.06% of methyl orange removal.